Pengaruh Perlakuan Benih secara Hayati pada Benih Padi Terinfeksi Xanthomonas oryzae pv. oryzae terhadap Mutu Benih dan Pertumbuhan Bibit - , Agustiansyah; Satriyas Ilyas; , Sudarsono; Muhammad Machmud (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
Bacterial leaf blight, the disease caused by Xanthomonas oryzae pv. oryzae (Xoo), a seedborne pathogen, has been known to reduce rice yield by 50%. In this study, two consecutive experiments were conducted in order to investigate the effect of various biological seed treatments applied on rice seeds artifi cially infected by Xoo on seed quality and seedling growth. Laboratory experiment was arranged in a completely randomized design while greenhouse experiment was arranged in a completely randomized block design. In both experiments, 12 seed treatments were applied: un-infected seeds (negative control) without seed treatment, Xoo infected seeds (positive control) without seed treatment, infected seeds soaked in bactericide Agrept 0.2%, infected seeds soaked in biological agent suspension isolate A6, infected seeds soaked in A54 isolate, infected seeds soaked in 5/B isolate, infected seeds soaked in 11/C isolate, infected seeds matriconditioned + A6 isolate, infected seeds matriconditioned + A54 isolate, infected seeds matriconditioned + 5/B isolate, and infected seeds matriconditioned + 11/C isolate. Soaking seeds either in Agrept 0.2% or in biological agent suspension was conducted for 30 h. Matriconditioning was conducted using ratio of seeds to carrier (burned rice hull 32 mesh) to biological agent suspension or bactericide solution of 1.0 (g) :0.8 (g): 1.2 (mL) for 30 h in air-conditioned room ca. 25 oC. Results of experiments showed that all biological seed treatments could suppress Xoo in rice seeds. Matriconditioning plus biological agent (isolate A6), biopriming with isolate A6 or isolate A54 were the best seed treatments to improve seed viability and vigor. In greenhouse experiment, matriconditioning plus isolate A54 was the best seed treatment to increase seedling growth.Keywords: biopriming, matriconditioning, rhizobacteria, seed health, viability